Energy metabolism dysfunction and therapeutic strategies for treating temporomandibular disorders - Gao, Wenjie; Gao, Zhiheng; Xiao, Heting; Qian, Yuchen; Fan, Rongkang; Li, Yonggang; Yang, Shaofeng; Yang, Yanjun; Qiao, Yusen (Frontiers in Medicine, 2025)
Temporomandibular disorders (TMD) are prevalent and multifactorial conditions affecting the temporomandibular joint (TMJ). Recent studies have highlighted the central role of energy metabolism in their pathogenesis. This review focuses on how disturbances in glucose, lipid, and mitochondrial energy pathways contribute to TMJ dysfunction and degeneration. The TMJ’s complex structure relies heavily on a balanced energy supply to maintain its physiological functions. Disruptions in glucose metabolism lead to oxidative stress, inflammatory cytokine release, and chondrocyte damage. Similarly, altered lipid metabolism—particularly imbalances in ω-3 and ω-6 fatty acids—modifies inflammatory responses. Hormonal influences, including cholesterol and estrogen, further exacerbate joint degeneration via signaling pathways such as Notch and NF-κB. These metabolic disturbances trigger cellular senescence, impaired matrix synthesis, and structural breakdown of cartilage and bone. The review also evaluates current and emerging therapeutic strategies. Standard treatments such as NSAIDs and corticosteroids relieve symptoms but fail to address underlying metabolic dysfunctions. Promising alternatives include intra-articular growth factors, metabolic modulators targeting oxidative stress, and autophagy inducers that restore mitochondrial balance. These approaches aim to correct cellular energy imbalances and support tissue regeneration. TMD involve significant metabolic dysregulation in the TMJ. Understanding the role of energy metabolism offers new insights into disease mechanisms and potential therapies. Future research should prioritize metabolic regulation as a target for long-term and disease-modifying treatments in TMD management.